Analisis Kemampuan Literasi Informasi Mahasiswa Program Studi Ilmu Perpustakaan dan Informasi Islam Angkatan 2023 UIN Raden Mas Said Surakarta dalam Penyusunan Makalah Menggunakan Model The Big Six - ASIFFA; Imam Mahmudi (Perpustakaan Universitas Riau, 2026)
AbstracInformation literacy is an essential skill that students must possess in searching, evaluating, and utilizing information to support academic activities, including paper writing. This study aims to analyze the information literacy skills of the 2023 students of the Islamic Library and Information Science Study Program at UIN Raden Mas Said in writing academic papers based on The Big Six model. This research employed a qualitative approach with a descriptive method. Data were collected through observations interviews, and documentation with students selected using purposive sampling techniques, then analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results showed that students were able to implement the six stages of The Big Six model, namely task definition, information seeking strategies, location and access, use of information, synthesis, and evaluation. Students utilized various information sources such as journals, books, Google Scholar, institutional repositories, and libraries. In addition, students conducted paraphrasing, citation, and systematic paper writing. Therefore, the information literacy skills of the students can be categorized as fairly good, although improvements are still needed in the use of more advanced information searching techniques and reference management applications.